2003
DOI: 10.1007/s00228-003-0657-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and allele frequency of CYP2D6 in Tamilian population

Abstract: The *10 allele is the most common mutant allele in Tamilians. The CYP2D6*4 and CYP2D6*5 alleles are distributed in a significantly different way in the Tamil population relative to Oriental populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…When they are compared to the results of Aynacıoğlu et al [21], allele frequencies and homozygous mutations turns out to be similar. This study's results were close to the ones found in previous studies in Asia, Sweden, Denmark, India, Malaysia, China, Japan, Europe [25][26][27][28].…”
Section: Resultssupporting
confidence: 89%
“…When they are compared to the results of Aynacıoğlu et al [21], allele frequencies and homozygous mutations turns out to be similar. This study's results were close to the ones found in previous studies in Asia, Sweden, Denmark, India, Malaysia, China, Japan, Europe [25][26][27][28].…”
Section: Resultssupporting
confidence: 89%
“…The frequencies of CYP2C9*2 in Indian population have found to be between 3–5 % whereas CYP2C9*3 ranges from 4–8 % [ 15 – 17 ]. The allele frequencies of *2 and *3 in Indian population published till date were found to be almost similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Except for our earlier study in Tamilians, 6) and a study done on North Indians at Mumbai on CYP2D6*4 allele, 12) there are no data available yet for CYP2D6 allele distribution in Indian populations.…”
mentioning
confidence: 84%